Deviant behavior of adolescents and socio-pedagogical conditions for its correction (SCIENCE and SOCIETY, 2023)
Socialization is a continuous process, that is, a person constantly interacts with society. Education is a continuous process. Because it is implemented in certain organizations and is limited in time and space. In particular, there are a number of socio-pedagogical factors for the prevention of negative behavior in the upbringing of minors, each of the- se factors has its own characteristics in the educational process. The article deals with the socio-pedagogical factors in the prevention of negative moral forms of adolescent behavior.